Parts, Axial Parts, and Next Parts in Kannada - Amritavalli, R. (Nordlyd, 2007)
Nouns meaning ‘place, region’ and ‘part’ are compounded in Kannada with a `bleached’ noun (a putative postposition) to form AxPart and Part readings. As in other languages, the AxPart or ‘region’ reading does not pluralize, does not permit adjectival modification, and allows for MeasureP modification (unlike the part reading). AxParts may also be formed out of nouns by the fusion of a dative marker or a genitive marker with the N; these case markers introduce the Place element. The dative case may be optionally overt (e.g. pakka-kke ‘side-dative,’ ‘to a side’), or covert (in AxParts like munde ‘front’). The genitive marker gives a sense of immediate adjacency that we designate the NextPart reading. Interestingly, the dative and genitive cases in Kannada also allow nouns to assume the function of predicative and attributive adjectives.
Keywords: bleached nouns; part and axpart compounds; dative case; covert genitive case; immediate adjacency; category change